PERLINDUNGAN KONSUMEN TERKAIT PEMBLOKIRAN IMEI DALAM PEMBELIAN SMARTPHONE LUAR NEGERI - Sekar Amialthoof (2024)
This thesis analyzes the legal protection of consumers who buy smartphones abroad regarding consumer smartphone IMEIs that are blocked by the government based on Permenkominfo No. 1 of 2020 about Registration and Control of IMEI (International Mobile Equipment Identity) connected with Law no. 8 of 1999 about Consumer Protection. This is done to find out the rules regarding blocking IMEI in Indonesia and the protection obtained based on the consumer protection law. The method used is normative juridical using secondary data, statutory approaches and case approaches. This article concludes that the IMEI blocking rules need to IMEI registration by passengers bringing from abroad or distributors. If a smartphone purchased from abroad is blocked, based on Law No. 8/1999, if it is carried by a passenger, the responsibility lies with the passenger as the importer, because the consumer protection law does not cover business actors abroad, whereas if purchased through a domestic distributor then the distributor can be held responsible.